Formalismo de primeira ordem para vórtices compactos em modelos generalizados - Zafalan, Ivanice (2018)
The purpose of this work is the compacts vortex study in generalized models. Thus, we started by reviewing some topics of Classical Field Theory, approaching essen- tially scalar fields in plane space. We review the study of some topological and non-topological defects such as kinks, lumps and vortex. Furthermore, we present original results such as two new models of generalized vortexes and two new models of generalized compacts vortexes for Maxwell-Higgs system. The latter shrink to a finite interval of the radial coordinate where solutions for energy density and mag- netic field vanish outside this range. We conclude present a first order formalism for generalized compacts vortex for which we arrive at the energy calculation without the explicit knowledge of the form of its solutions.